Nonlinear Origin of SSVEP Spectra—A Combined Experimental and Modeling Study - Labecki, Maciej; Kus, Rafal; Brzozowska, Alicja; Stacewicz, Tadeusz; Bhattacharya, Basabdatta S.; Suffczynski, Piotr (Frontiers in Computational Neuroscience, 2016)
Steady State Visual Evoked Potentials are the steady-state oscillatory potentials elicited in the EEG by flicker stimulation. Frequency of these responses corresponds to the stimulus frequency, its harmonics and subharmonics. In this study we investigated the origin of harmonic and subharmonic components, which are not well understood. We applied both sine and square visual stimulation at 5 and 15 Hz in human subjects and analyzed the properties of fundamental responses and harmonically related components. In order to interpret these results we used well-established lumped alpha rhythm model describing interacting populations of excitatory and inhibitory cortical neurons. The model offers a simple explanation for the origin of SSVEP spectra. It shows that their harmonic and subharmonic components are a natural consequence of nonlinear properties of neuronal populations and resonant properties of the network. The model also predicted multiples of subharmonic response, which were subsequently confirmed using experimental data.